Language and Violence: A Gender-Based Analysis of Verbal Bullying Among Students - Yusri, Yusri (Universitas Negeri Makassar, 2024)
This study aims to analyze the types of verbal bullying most often experienced by students and identify differences in experiences based on gender factors. Using a quantitative approach, data were collected from school students through a survey and analyzed to reveal patterns of verbal bullying. The results showed the three most dominant types of verbal bullying: name-calling, insults, and teasing. In addition, further analysis showed that the experience of verbal bullying was influenced by gender factors, with patterns and intensity varying between male and female students. These findings highlight the need for school policies and intervention programs that consider gender aspects to create a safe and bullying-free learning environment. This study makes an essential contribution to efforts to prevent verbal bullying, both through educational approaches and evidence-based policies.